PENGELOLAAN PROGRAM CSR PT SUCOFINDO DALAM MENINGKATKAN EKONOMI BERKELANJUTAN DI PERUMDA PASAR JAYA - Rangga Tri Wijaya (2023)
This study aims to find out how to manage a Corporate Social Responsibility (CSR) program carried out by PT Sucofindo to improve a sustainable economy at Perumda Pasar Jaya, as well as knowing who the stakeholders are involved and what is the role of each of these stakeholders, using the concept of Public Management. Stakeholder relations and theory. This research uses descriptive qualitative method. The sources obtained in this study were obtained through interviews, literature studies, and documentation studies. In this study, there was one key informant and three informants, namely the Head of the CSR Division of PT Sucofindo as the key informant, two members of the PT Sucofindo CSR team as informants, and one other informant, the Assistant Manager of Pasar Mayestik as the beneficiary. In this study using three steps of data analysis, namely, data reduction, data presentation, and verification or conclusions with data triangulation. The results of this study state that in managing PT Sucofindo's CSR program to improving a sustainable economy at Perumda Pasar Jaya there are four stages, namely problem identification, planning, implementation, and evaluation. In carrying out the CSR program, PT Sucofindo uses the concept of Creating Share Value (CSV), and this CSR activity is a form of the company's commitment to contributing to society, which in this case returns economic value to the Mayestik Market. In the CSR activities carried out there were stakeholders who were involved in PT Sucofindo's CSR program activities, including the CSR Team, Serco Unit, Pasar Jaya, Mayestik Market, Ministry of BUMN, and the Community. Each of them has an important role in participating in helping PT Sucofindo's CSR activities take place.